Evaluation of elearning usage in South African universities: A critical review - Bagarukayo, Emily (International Journal of Education and Development using ICT, 2015)
Although eLearning is the use of technology for teaching, learning and assessment, there is no common approach to it across South African Higher Education Institutions. There is therefore a concern that the full potential of eLearning approach is not utilised. This paper examines the nature and the extent of eLearning activities in South African (SA) universities. The research method employed in this paper was informed by a literature review; sources from the last decade include journals, conferences, books and websites. The findings show that the level of eLearning usage and adoption varies in different universities due to several challenges such as those of technology and institutions. We give an overview of studies conducted in eLearning in SA universities, highlighting challenges and best practices. We recommend management involvement of faculties in policy decisions and investment in technological innovations to address these challenges issues.
Keywords: eLearning; eLearning Challenges; Learning Management Software; Social Software